Classification of economic parameters and data among the functional blocks of the telecommunications management system - Jikia, Anna; Kurashvili, Izolda; Kurdadze, Marina (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2023)
The paper discusses the most important signs, according to which the classification of information flows (data) is carried out, in the case when the connections between the functional blocks of the management system are considered, it is noticeable that a change in one functional part causes a certain change in another part of it, but this does not affect the existence of a connection between them. When the management system is an information system, the connections in it were also informative. The generalized structure of telecommunications systems and networks allows this service area to be accessible and understandable to users and the management team of any industry, how functional blocks can be presented in a single space of classifications, and the generalized structure is presented as.